2015
DOI: 10.1007/s10854-015-3109-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reaction temperature on surface morphology and photoelectric properties of ZnO grown by hydrothermal method in mixed solvent

Abstract: ZnO thin films were prepared by hydrothermal method in mixed solvent with different reaction temperatures. Microstructure, surface morphology, optical properties and UV photoresponse of the thin films have been investigated by means of X-ray diffractometer, scanning electron microscopy, laser micro-Raman spectrometer, UV-Vis spectrophotometer and interactive source meter instrument. The results indicated that ZnO thin films consist of ZnO nanoparticles with hexagonal wurzite structure. A small quantity of Zn(O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Previous reports have indicated that lattice mismatch between ZnO and sapphire could persist even in a film as thick as 1 μm, leading to a redshift of 50 meV for the band-edge emission peak [ 45 , 46 ]. In addition, variations of the surface morphology and oxygen vacancy population are also the factors that cause this change [ 47 ]. The PL emissions of the two ridge-like films exhibit much stronger intensities with FWHMs of 123 and 133 meV for ZnO-R1 and ZnO-R2, respectively, which are smaller than that of the particle-like sample and smaller than that of a ZnO film grown on the (111) plane of cubic YSZ [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have indicated that lattice mismatch between ZnO and sapphire could persist even in a film as thick as 1 μm, leading to a redshift of 50 meV for the band-edge emission peak [ 45 , 46 ]. In addition, variations of the surface morphology and oxygen vacancy population are also the factors that cause this change [ 47 ]. The PL emissions of the two ridge-like films exhibit much stronger intensities with FWHMs of 123 and 133 meV for ZnO-R1 and ZnO-R2, respectively, which are smaller than that of the particle-like sample and smaller than that of a ZnO film grown on the (111) plane of cubic YSZ [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, a green emission band appears at approximately 2.5 eV in ZnO-P, which is similar to that of a ZnO film deposited on MgO(100) [ 49 ]. In general, oxygen vacancies [ 50 ], surface morphology [ 47 , 51 ], and oxygen clusters formed on the surface [ 52 ] are major origins for the green emission band. ZnO films with densely vertically aligned ZnO nanorods have been reported to possess stronger green emission bands relative to films with small particle and nanosheet morphologies [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation was 42.5%, 64.6% and 98.3% for the Ti/TiO 2 /CdS‐CNT/C 3 N 4 electrode in the EC, PC and PEC reaction conditions, respectively. It was obvious that PEC efficiency of Ti/TiO 2 /CdS‐CNT/C 3 N 4 electrode is almost the summation of EC and PC efficiency because of the photoelectric synergy …”
Section: Resultsmentioning
confidence: 99%
“…76 Small pyramidal particles, ZnO NSs and NRs can also be controlled by changing growth temperatures. 77 Different reaction times affected 61 (d) Ostwald ripening mechanism for the formation of mesoporous hollow spheres (Copyright@ Elsevier 2018. All rights reserved, reprinted with permission).…”
Section: + → ( ) [ ]mentioning
confidence: 99%